Industry 4.0 Evolutions - Technical Education for Sustainable Social Development - Gumparthi, Srinivas (International Journal of Advanced Science and Technology, 2020)
Industry 4.0 has potential to change significantly the knowledge and skill-set requirements for Employability of Engineers and Management Professionals; Industry 4.0 forcing Academic and Research Institutions to rethink and assess capabilities of Engineers and Management professional to avoid a problems in smooth adaptation to the transformational changes happening in every sphere of society. This project examines the likely impacts of Industry 4.0 on Engineering Management Education. Also proposes enhancements to Engineering and Management curricula in India. Research methods include a literature review, a study of Undergraduate and Post Graduate curricula of both Engineering and Management education, and a questionnaire survey of programmes of Various reputed universities. Preliminary study indicates that several Engineering and Management functions might become somewhat transformed, less visible, or downright diminished in Industry 4.0. Emphasis has shifted from traditional Engineering and Management methods to data-driven functions and cyber-physical systems. The developing mismatch needs correcting by emphasising skills such as ‘big data’ analytics and novel human-machine interfaces in Engineering and Management curricula. Only few universities (Specially Private Universities) in India have made progress towards the adoption of an Industry 4.0 infrastructure. The researchers propose a set of curriculum enrichment items as the basis for reform..